W(h)ere There’s a Wolf, There’s a Way: Lupine Masculinities in Mongrels and Where the Dead Sit Talking - Gamber, John (Transmotion, 2023)
This essay places the lyconthropic representations in Stephen Graham Jones’ (Blackfeet) Mongrels (2016) in conversation with those (and the more broadly lupine) in Brandon Hobson’s (Cherokee) novel, Where the Dead Sit Talking (2018). Both novels wield their lupine imagery (of werewolves and wolves) as devices to interrogate the tensions and overlaps between a series of dichotomies triangulated through their respective constructions of masculinity, notably: the (masculine) wild and the (feminine) domestic; solitude and community; and motion and stasis. Ultimately, WDST puts forth a protagonist who is more ambivalent to the (feminized) domestic sphere and who cultivates various feminine elements of himself, while generally opting out of the social elements of community. Mongrels, however, offers a protagonist who initially denies his responsibilities to community, which he sees as antithetical to the masculine wolf he longs to be, and, rather, akin to the feminine human he maligns.